Contrasting metamorphic terranes near Chéticamp, Cape Breton Highlands, Nova Scotia - Currie, K. L. (Canadian Journal of Earth Sciences, 1987)
Two contrasting metamorphic terranes can be recognized in northwestern Cape Breton Island. One terrane (Pleasant Bay complex) consists of biotite gneiss and quartzite with minor calc-silicate lenses that were metamorphosed in Late Precambrian time (about 550 Ma) and were subsequently intruded by Silurian salic and mafic plutons that were, in turn, deformed and intruded by granite in Devonian time. The other terrane (Jumping Brook complex) consists of volcanogenic and sedimentary schists of probable Silurian age that were metamorphosed in Devonian time. P–T estimates indicate that the older parts of the Pleasant Bay complex were metamorphosed at about 790 °C and 7 kbar (1 kbar = 100 MPa) at low to moderate water fugacities during a major intrusive episode. The Jumping Brook complex exhibits a single progressive metamorphic sequence now disrupted by faulting. P–T conditions during this Devonian (370–390 Ma) metamorphism varied from greenschist (300 °C at <3 kbar) to amphibolite (650 °C at 4 kbar) facies. Metamorphism probably occurred in a thermal dome. The data suggest a moderately deformed basement–cover relation between the Pleasant Bay and Jumping Brook complexes.